The Impact of Teachers’ Differentiated Instructions on Gifted Students at a Private School in Abu Dhabi - MAKAWI, SAWSAN EMAD (2025)
This study examines the effectiveness of differentiated instruction for gifted students within a private school in Abu Dhabi. The research investigates the impact of educators’ behaviours and instructional strategies on the learning experiences of gifted students, placing particular emphasis on advanced questioning, inquiry-based learning, flexible grouping and the implementation of appropriate educational resources technology. Grounded in a philosophical foundation based on the social constructivist worldview, classroom observations and interviews were conducted to gather empirical data from teachers and educational leaders. Results revealed that while some differentiation strategies are effectively implemented and positively impacted gifted and talented students’ learning experiences, inconsistencies and challenges such as time constraints, classroom management and a lack of targeted professional development impede their consistent application. The study highlights the significance of supportive school leadership and access to resources and technology in fostering effective differentiation. The results underscore the imperative for continual professional development and collaborative planning to augment educators’ ability to address the varied requirements of gifted students, with the ultimate objective of fostering their academic advancement and engagement.